1994
DOI: 10.1111/j.1748-5827.1994.tb03953.x
|View full text |Cite
|
Sign up to set email alerts
|

M‐mode echocardiography study in growing Spanish mastiffs

Abstract: The growth of the heart in proportion to bodyweight was studied by M-mode echocardiography in 66 Spanish mastiffs aged from one to 12 months and from two to four years. Measurements of the right and left ventricular cavities, septal and parietal wall thicknesses, aorta, left atrium, D-E excursion of the mitral valve and distance between the maximum aperture of the mitral valve and the interventricular septum, were shown to have a curvilinear increase closely related to the development of bodyweight. Least squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 18 publications
7
33
0
1
Order By: Relevance
“…In line with previously published data in growing ponies and Thoroughbred foals [14,28] and in dogs of different breeds [2,3,10], several echocardiographic measurements increased progressively with age in our study, although the groups of age between which significant differences existed varied according to the echocardiographic parameter. The most marked increases in the dimensions of chambers (AOD, ABS, AJT and LV), LVFWT and IVST were found between groups B and C for the fillies and between groups D and E for the colts.…”
Section: Comparison Of the Echocardiographic Measurements In Spanish supporting
confidence: 92%
See 1 more Smart Citation
“…In line with previously published data in growing ponies and Thoroughbred foals [14,28] and in dogs of different breeds [2,3,10], several echocardiographic measurements increased progressively with age in our study, although the groups of age between which significant differences existed varied according to the echocardiographic parameter. The most marked increases in the dimensions of chambers (AOD, ABS, AJT and LV), LVFWT and IVST were found between groups B and C for the fillies and between groups D and E for the colts.…”
Section: Comparison Of the Echocardiographic Measurements In Spanish supporting
confidence: 92%
“…However, other authors found that young animals have a better myocardial contractility, because of the lower peripheral vascular resistance and/or of the higher HR. Therefore, higher values for FS%, FWT% and FST% were found in puppies [3]. In addition, Della Torre et al [7] demonstrated that FS% is greatly influenced by BW, with large dogs having lower values than small dogs.…”
Section: Comparison Of the Echocardiographic Measurements In Spanish mentioning
confidence: 99%
“…Some investigators have shown a nonlinear relationship between cardiac dimensions and body weight in dogs throughout their postnatal growth period, but the nonlinear relationship was observed primarily at very young ages (with animals of smaller body weights), and relatively linear associations were found in older dogs (with greater body weights). 13,14 Other investigators demonstrated a linear relationship between cardiac dimensions and body weight for adult dogs weighing 4.5-30 kg, similar to our observations. 8 Finally, we have not examined dogs with left-heart disease.…”
Section: Study Limitationssupporting
confidence: 82%
“…9,19,20 Other investigators have utilized power regressions against W of the form YЈ ϭ AW B , where A and B were the model parameters to be estimated. 9,19,20 The exponent (B) from power regressions for dogs in this study was never demonstrably different from the constant shape value of ⅓. Exponent values from earlier reports have been similar, and it has been noted previously that ⅓ is the analytically correct value.…”
Section: Discussionmentioning
confidence: 99%